EFFECT OF INTRA VITREAL INJECTION OF BEVACIZUMAB ON INTRA-OCULAR PRESSURE - Jaffar, Sulman; Tayyab, Ali; Matin, Zeba Illyas; Masrur, Amena; Naqaish, Rehan (Journal of Ayub Medical College Abbottabad, 2016)
Background: Bevacizumab has been in use as a therapeutic agent for macular oedema for several years. While its efficacy has been well documented, its use has been shown to cause a transient rise in the intra-ocular pressure. The aim of this study was to evaluate the long term effect of intra-vitreal injection of Bevacizumab on Intra-ocular pressure. Methods: One hundred eyes (n=100) of one hundred patients, requiring intra-vitreal injection of Bevacizumab for diabetic macular oedema were recruited from Shifa Foundation Community Health Centre (SFCHC) between January and December 2014. Patients of glaucoma, ocular hyper-tension, known allergy to Bevacizumab or had injections of Bevacizumab prior to the study were excluded. Intra-ocular pressure was measured using a Goldmann applanation tonometer, prior to, and at six and twelve months after the injection. The pre- and post- injection Intra-ocular pressure was entered into the database. Test of significance was applied to investigate whether there was a significant change in intra-ocular pressure after the injection. Results: The mean age of the patient was 56.97 years (±14.97). The mean intra-ocular pressure was 13.86 (±3.16) mmHg before injection, while post-injection mean Intra-Ocular pressure was 14.21 (±3.12) mmHg and 13.79 (±3.07) at six and twelve months respectively. Between baseline and six months there was a statistically significant difference in intra-ocular pressure (p=0.03), while no significant difference existed in the intra-ocular pressure between baseline and twelve months (p=0.92). Conclusion: Intra-vitreal injection of Bevacizumab is associated with a statically significant rise in intra-ocular pressure at six months, while no significant difference was seen at twelve months compared to baseline Keywords: Bevacizumab, intra-ocular pressure, intra-vitreal, injection